2018
DOI: 10.18203/issn.2454-5929.ijohns20180705
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of accessory ostia in patients with chronic maxillary sinusitis

Abstract: <p class="abstract"><strong>Background:</strong> <span lang="EN-IN">Chronic maxillary sinusitisis is one of the most frequent diseases presenting in ENT out patient department seeking medical attention<sup>.</sup><strong> </strong>Defects in the fontanelle region of the lateral nasal wall have been described as accessory ostia. The presence of AMO in both pre and post operated cases of chronic maxillary sinusitis can cause recirculation of mucus leading to recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 10 publications
3
14
0
Order By: Relevance
“…[6] In our study there was no statistically signi cant difference in the occurrence of AMOs between male and female subjects, although the occurrence was numerically higher in male subjects. Similar observations were found in the studies by Bani-Ata et al and Ghosh et al [1,7] However, Hung K et al found AMOs to be more commonly present in, CBCT scans of female subjects. 9 It is important to note that there was no statistical difference in terms of gender in any of the studies reiterating the fact that, gender had no signi cant in uence on the occurrence of AMO.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…[6] In our study there was no statistically signi cant difference in the occurrence of AMOs between male and female subjects, although the occurrence was numerically higher in male subjects. Similar observations were found in the studies by Bani-Ata et al and Ghosh et al [1,7] However, Hung K et al found AMOs to be more commonly present in, CBCT scans of female subjects. 9 It is important to note that there was no statistical difference in terms of gender in any of the studies reiterating the fact that, gender had no signi cant in uence on the occurrence of AMO.…”
Section: Discussionsupporting
confidence: 86%
“…[6,20,21] In another CT and endoscopy-based research on the Indian population conducted in 2018, AMOs were found in 23 percent of the cohort. [1] Similar percentages were reported by purely endoscopic studies in the Indian population. [19] AMOs were reported in 13.8-26% of the cadavers as per few recently study published anatomical studies.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…1 Another study also showed this association and recommended including the posterior or anterior fontanelle when performing middle meatal antrostomy to reduce mucus recirculation. 2 In addition, Capelli et al found that maxillary mucosa thickness ≥2 mm and closure of the natural maxillary ostium were significantly associated with chronic rhinosinusitis; common anatomical variants, including concha bullosa, Haller cells, and accessory maxillary ostia, were not. 13 Yenigun et al reported that the presence of accessory maxillary ostium was associated with an approximately threefold increase in the incidence of mucus retention cysts and a two-fold increase in the incidence of mucosal thickening and maxillary sinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…The accessory ostium of the maxillary air sinus is an anatomical variation that may play a role in the development of chronic sinusitis. 1,2 Accessory maxillary ostia are most commonly located in the posterior nasal fontanelle of the middle meatus and may occur unilaterally or bilaterally. 3,4 Accessory maxillary ostium is usually located on the lateral nasal wall, and should not be confused with the maxillary hiatus.…”
Section: Introductionmentioning
confidence: 99%